The Role Of Digital Marketing In Enhancing Customer Engagement For Social Media–Based Local Entrepreneurs - Sudarso, Hendri; Hakim, Lukman; Indra, Ricardo; Mani, La (Jurnal Minds: Manajemen Ide dan Inspirasi, 2026)
This study examines the effect of digital marketing on customer engagement among Micro, Small, and Medium Enterprises (MSMEs) in Bengkalis Regency. Specifically, it investigates how social media marketing, content marketing, and online customer interaction influence behavioral and emotional engagement. A quantitative approach with an explanatory research design was employed, using Structural Equation Modeling – Partial Least Squares (SEM-PLS) on 250 MSME respondents who actively use social media. Data were collected via online questionnaires distributed through social media and community networks. The results indicate that content marketing and online customer interaction significantly enhance behavioral engagement, while social media marketing and content marketing significantly increase emotional engagement. Conversely, social media marketing does not affect behavioral engagement, and online customer interaction does not affect emotional engagement. These findings suggest that MSMEs should prioritize value-driven content and authentic interactions to foster meaningful customer engagement.